Pray bold : dare to ask and believe big - Osteen, Joel (Faith Words, 2025)
"At any given moment, God is ready to jump into our lives and act on our circumstances. But we spend so much time overwhelmed by the demands of daily life that we forget the amazing power we have access to as children of God. Our lives are dull and our situations don't change because we are not asking God for the bold desires that are in our hearts. Instead of praying that God will help you survive the day of work at a dead-end job, pray that God will open the doors for you to have your dream job at your dream company. Instead of praying that God will keep you and your spouse from getting a divorce, pray that God will light the way to making your marriage happy and thriving again. There is a clear pathway between what we think, what we ask for, and what God does. Transform your life by starting a new way of thinking, asking boldly, and believing big!"--